Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1177/014556130508400514
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ligation of the Sphenopalatine Artery as a Primary Management of Severe Posterior Epistaxis in Patients with Coagulopathy

Abstract: We describ e our experience with endoscop ic ligation ofthe sp henopalatine artery in the treatment ofsevere posterior ep istaxis in 2 patients with coagulopathy. Conservative treatment had failed in both cases. The key elements of this procedure are the identification of the branches of the sphenopalatine art ery via an endoscopic endonasal approach and the appli cation oftwo titanium clips under direct vision. Thisprocedure was successful in bothpatients, and we recomm end it in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The sphenopalatine artery is the terminal branch of the internal maxillary artery and the dominant source of posterior nasal blood supply. Endoscopic ligation of the sphenopalatine artery causes interruption of the nasal vasculature at a point distal enough to prevent direct, retrograde and anastomotic blood flow from ipsilateral and contralateral carotid systems 7 …”
Section: Introductionmentioning
confidence: 99%
“…The sphenopalatine artery is the terminal branch of the internal maxillary artery and the dominant source of posterior nasal blood supply. Endoscopic ligation of the sphenopalatine artery causes interruption of the nasal vasculature at a point distal enough to prevent direct, retrograde and anastomotic blood flow from ipsilateral and contralateral carotid systems 7 …”
Section: Introductionmentioning
confidence: 99%
“…5 Direct cauterization, external carotid artery ligation, selective maxillary artery embolization, transantral maxillary artery ligation, anterior ethmoidal artery ligation and septoplasty are some of the other options for control of posterior epistaxis. 6 Yet none of these treatments is ideal.…”
Section: Discussionmentioning
confidence: 99%
“…9 and hemostatic clips to the sphenopalatine vessels via a transnasal endoscopic route in 10 patients with intractable epistaxis and they also reported a success rate of 100% . 6 Multiple studies have reported a success rate of over 90% with no significant complications. 9,10 This study reports a success rate of about 88% in controlling the posterior epistaxis.…”
Section: Traditional Surgical Procedures For Intractablementioning
confidence: 99%
“…The complications of this procedure have been extensively reported in the literature and include hemiplegia, ophthalmoplegia, facial paralysis/paresthesia, blindness, or other neurological deficits caused by accidental embolization of cerebral arteries [ 18 , 32 , 33 ]. These possible complications were shown to occur in up to 27% of cases [ 18 , 20 ].…”
Section: Nonsurgical Interventionsmentioning
confidence: 99%